Tsukushi proteoglycan maintains RNA splicing and developmental signaling network in GFAP-expressing subventricular zone neural stem/progenitor cells - Istiaq, Arif; Umemoto, Terumasa; Ito, Naofumi; Suda, Toshio; Shimamura, Kenji; Ohta, Kunimasa (Frontiers in Cell and Developmental Biology, 2022)
Tsukushi (TSK) proteoglycan dysfunction leads to hydrocephalus, a condition defined by excessive fluid collection in the ventricles and lateral ventricular (LV) enlargement. TSK injections in LV at birth is effective in rescuing the LV development. TSK regulates the activation of the Wnt signaling to facilitate the proper expansion of LV and maintain the fate of the neural stem cell lineage. However, the molecular mechanism by which TSK acts on neural stem/ progenitor cells (NSCs) during LV development is unknown. We demonstrated that TSK is crucial for the splicing and development associated gene regulation of GFAP-expressing subventricular zone (SVZ) NSCs. We isolated GFAP-expressing NSCs from the SVZ of wild-type (GFAPGFP/+) and TSK knock-out GFAP-GFP (GFAPGFP/+/TSK-/-) mice on postnatal day 3 and compared their transcriptome and splicing profiles. TSK deficiency in NSCs resulted in genome-wide missplicing (alteration in exon usage) and transcriptional dysregulation affecting the post-transcriptional regulatory processes (including splicing, cell cycle and circadian rhythm) and developmental signaling networks specific to the cell (including Wnt, Sonic Hedgehog, and mTOR signaling). Furthermore, TSK deficiency prominently affected the splicing of genes encoding RNA and DNA binding proteins in the nervous SVZ and non-nervous muscle tissues. These results suggested that TSK is involved in the maintenance of correct splicing and gene regulation in GFAP-expressing NSCs, thereby protecting cell fate and LV development. Hence, our study provides a critical insight on hydrocephalus development.